If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + -1(x + 2) + 3x = 7 Reorder the terms: 1 + -1(2 + x) + 3x = 7 1 + (2 * -1 + x * -1) + 3x = 7 1 + (-2 + -1x) + 3x = 7 Combine like terms: 1 + -2 = -1 -1 + -1x + 3x = 7 Combine like terms: -1x + 3x = 2x -1 + 2x = 7 Solving -1 + 2x = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 2x = 7 + 1 Combine like terms: -1 + 1 = 0 0 + 2x = 7 + 1 2x = 7 + 1 Combine like terms: 7 + 1 = 8 2x = 8 Divide each side by '2'. x = 4 Simplifying x = 4
| 3x-5+x=5x-10 | | 9/9-1 | | 3b-2-b=8 | | 3/2(5x+1)=4(3-2x)+5 | | 5x+2=9x-8 | | 35+5x=100+8x | | 15=-2+-1d | | -45a=15 | | 3x/2=12 | | 18-4c=22 | | 2x-6=2x+9 | | 0.5x*0.2=0.9x-2.6 | | -7w=-12 | | 42x=0 | | 5x-3-x=2x-15 | | 0.5x*0.2=0.9-2.6 | | (X/-5) | | ln(x)=3.03 | | x+3=5-x | | 3n-4=90 | | 2X+57=180 | | X^2-5=3x | | -9(w+8)=3w-12 | | 3x-3=-2x+22 | | 150x+1000=22000 | | -3f+1=4 | | 3(2a+7)=5a+22 | | (X+3)/2=14 | | 7-(-4y)=4t-14-21t | | -106-7x=-31-9x | | 2*1+4y=8 | | x/8+x/9=17/72 |